Barriers in Nursing Practice in Cancer Cachexia: A Scoping Review - Rika Sato; Tateaki Naito; Naoko Hayashi (Elsevier, 2021)
This scoping review aims to identify the barriers in practice and clinical trials for oncology nurses in cancer cachexia. We used the framework proposed by Arksey and O'Malley and Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews. Studies written in English and published between 2008 and 2021 were retrieved from five databases: MEDLINE, Cochrane Library, CINAHL, PsycINFO, and EMBASE. A total of 1075 studies were identified, and 34 full-text studies were assessed for eligibility by three researchers. Seventeen studies met the inclusion criteria. This review revealed several barriers to nursing practice and clinical trials in cancer cachexia. First, health-care professionals, including nurses, faced individual barriers (insufficient understanding and skills for diagnosis and management) and environmental barriers (lack of standardized screening tools or treatment options, difficulties in collaboration with other professions, and limited human resources) in practice. Second, studies on nurse-led interventions for cancer cachexia were relatively few and different in objectives, making it challenging to integrate the outcomes. Finally, there were no established educational programs for nurses that explicitly focused on cancer cachexia. This scoping review revealed individual and environmental barriers in nursing practice. In addition, there have relatively few clinical trials involving oncology nurses in cancer cachexia. Continuing education for nurses should cover cancer cachexia to improve the quality of oncology care in the future. It is also necessary to standardize practical assessment tools that are easy to assess daily and lead to interventions and develop nurse-led multidisciplinary care.